Meningkatkan Partisipasi Masyarakat Dalam Upaya Pencegahan Dan Penanggulangan Bencana Longsor Di Desa Gelangsar Kabupaten Lombok Barat : - - Muhammad Ramadhan; Zulfa Aulia Hasni; Nurfitriani; Santi Farmasari; Anggi Wiraning Palupi; Sumaiyah; Latifha Padlani (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
This community service program was conducted in Gelangsar Village, West Lombok. It was aimed at increasing the villagers’ awareness and participations in preventing and surviving natural disasters. The prevention programs were conducted by involving the villagers to get actively involved in rubbish management, whereas the disaster survival programs were conducted by training the villagers the first-aid skills for the safety of their selves and for other villagers’. The programs were successful because of the supports of the village local officials, the villagers, as well as from other institutions: the Department of Social and the Department of Local Disasters Management.